Shear and crushing strengths of wood pellets - Spirchez Cosmin (Revista Drewno, vol.59, Nr.198, anul 2016, 2016)
This paper presents a methodology for determining the shear and crushing strengths of four types of wood pellets. Wood pellets are renewable and sustainable products that are obtained from wood biomass and used in combustion. Their mechanical characteristics are not well defined. To characterize wood pellets, their shear and crushing strengths should be measured along with their size, moisture content, density, abrasion, and chemical contents. The shear and crushing strengths were analysed for their dependence on density, considering if these strengths remain as independent properties or only an additional option for the producers. All results showed that the shear and crushing strengths were individual properties of wood pellets and that density greatly influenced these properties. Based on theoretical research, the admittance values of breaking and shear strengths were also estimated. These results can be used in wood combustion for creating fuels from waste wood.